Political Communication of Female DPRD Members of Langkat Regency in Winning the 2019 Legislative Election - Nanang Susianto; Anang Anas Azhar; Efi Brata Madya (Journal of Law, Politic and Humanities, 2024)
This research aims to analyze: (1) Analyze the Political Communication Strategy of Female DPRD Members of Langkat Regency in Winning the 2019 Legislative Election (2) Female DPRD Members of Langkat Regency improve their political image in Winning the 2019 Legislative Election. (3) Female DPRD Members of Langkat Regency succeeded in winning the 2019 Legislative Election. This research uses descriptive methods and a qualitative approach. Using a qualitative approach or often called the Naturalistic method because this research is used in natural conditions (natural settings). Research results; The Political Communication Strategy for Women DPRD Members of Langkat Regency in Winning the 2019 Legislative Election is first: Socialization with citizens is carried out by starting with identification, determining voting centers and embracing permanent voters again. Second, family socialization for legislative candidates. Family influence can also be seen in their choice of political party. Thirdly, political campaigns depend on many factors, including career paths, political communicators, constituents, message strategies and communication media channels. Fourth Women's Community Where women's communities in Langkat Regency are approaching using digital campaigns. Fifth, Form a Winning Team of people trusted by the candidate, for this reason you need to be careful in recruiting to be able to join the campaign team. Female DPRD members of Langkat Regency improve their political image in winning the 2019 Legislative Election. First is the issue of women's representation. Representation of women to become legislative members in Langkat Regency. Second Marketing Concept for Female Legislative Candidates The urgency of women's representation. Langkat Regency Female DPRD members succeeded in winning the 2019 Legislative Election.